PENGARUH MATA KULIAH KEWIRAUSAHAAN DAN PRAKTIK KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN ANGKATAN 2021 UNIVERSITAS NEGERI MEDAN - Imelda Sidabutar; Nelly Armayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the Influence of Entrepreneurship Courses and Entrepreneurship Practices on Entrepreneurial Interests of Office Administration Education Students Class of 2022, State University of Medan. The population in this study was 88 students. This study uses a quantitative method with a sampling technique using the total sampling method. So that the population used as a sample is 88 students. The data collection instruments used are in the form of observation and questionnaires. The data analysis technique used in this study is multiple linear regression analysis with hypothesis testing, namely Partial Test (T Test), Simultaneous Test (F Test), and Coefficient of Determination (R²). Based on the analysis that has been carried out, the results obtained Entrepreneurship Courses have a significant influence on Entrepreneurial Interests of Office Administration Education Students Class of 2022, State University of Medan. Then Entrepreneurship Practices have a significant effect on Entrepreneurial Interests of Office Administration Education Students Class of 2022, State University of Medan. From the results of this study it can be concluded that if someone has in-depth entrepreneurial knowledge then supported by entrepreneurial practices and the will to become an entrepreneur then their interest in entrepreneurship will increase and the individual will have greater success in the world of entrepreneurship.